As capacitações e os recursos logísticos para a prática do Supply Chain Management (SCM) - Marchesini, Márcia Maria Penteado (2005)
Within the current context of competition, we can perceive the emergence of a new paradigm of business management based on the fact that companies no longer compete isolatedly or individually among themselves, but through the various supply chains they belong to. This new paradigm or concept of management refers to Supply Chain Management (SCM). Particularly, logistics has a significant impact on the SCM concept and represents the fundamental process for this concept as it propitiates the operational arrangement of the supply chain. Thus, this dissertation searched to identify the effects of the adoption of the concept of SCM and its initiatives in the logistic function of the distribution channel companies of grocery products, generating, through the Resource Based View (RBV) as classification approach, the identification of logistic capabilities and resources. For in such way, there was an ample discussion about the concept of SCM and its different views and definitions. In this context, the needed logistic capabilities and resources to adopt SCM concepts and initiatives were identified in the bibliographical revision of this research. This dissertation, through this ample discussion, will contribute to the more development of SCM theory and of unification of the logistic theory. There were various logistic capabilities, like the adoption of logistics function as a strategic activity, the adoption of concept of integrated logistics, the adoption of Lean and Agile Paradigm or Re-supplying. Additionally, there were various logistic resources, like IT (Information Technology) and its tools, the software related to logistics and Logistics Information System, crossdocking. To complement the theory discussion about SCM and logistic capabilities and resources, this research realized three case studies, whose object was to evaluate the adoption and the degree of development of these logistic elements, through the contrast between encountered theory and practice, and identify the main benefits to each company, the expected results but not reached and the main logistic problems faced for each company. With the results from these three cases, there was good adoption in the practice of logistic capabilities and resources, the literature emphasized, independently the degree of development in each company. However, it was evident the discrepancy among the researched companies as for the adoption and use of the logistic change points existent in the literature, and their development degree, that allowed suggest a hierarchy of companies in terms of the implantation of logistic capabilities and resources. Specifically, this dissertation holds a qualitative research approach, as investigative method the multiple case studies, as the instrument of data collection the interview which was carried out by semi-structured questionnaire.